La transparencia como mecanismo proyectual - Muxí, Zaida, Pérez, Fabián Gabriel (2001)
Entrevista a <RCR Arquitectes> en Olot, España
Keywords: ARANDA, RAFAEL; ENTREVISTAS; PIGEM BARCELÓ, CARME; VILALTA PUJOL, RAMÓN; ESPAÑA; OLOT; ARQUITECTURA